A Arte como Elemento de Crítica na Crise da Cultura - Tavares Jr, Carlos A. (Universidade de São Paulo | Escola de Comunicações e Artes, 2012)
When the arts firstly remain the human’s intellectual capability of thinking and the philosophic ambit, there are a justification which requires an abstraction moment and relativized production in front of “hard sciences”. However, when the arts come to be referred by György Lukács as way to rethink how the decreased human’s relationships due to socioeconomic practices were magnified by the capital reification. Therefore, Lukács, along his intellectual course, have changed his own backbone concepts in many times, to show how the total ways of hermeneutics lead the culture to a crisis in front of the history and culture dialectic mobility.